Хозяйка книжного магазина - Солнцева Наталья Михайловна (Мистический детектив, 2019)
Экземпляры: ЦБ (20200317) / Инвентарный номер: 52043 / Цена: 255.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 60 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44